Uso do solo do Rio Poxim-Açu/SE : modelagem e construções de cenários conservacionistas - Matos, Alda Lisboa (2013)
The soil usage as well its occupation tend to be increasingly influenced by a number of pressures emanating from its relationship with the environment. This is due to the urgency to maintain the balance between natural ecosystems and the increasing demand to occupy new territorial areas. The cover has important role in the process of securing land and favor maintaining the quantity and quality of water. The areas occupied by agriculture and pasture are more likely to suffer from erosion processes. In these environments the watercourses may also be affected by excess sediment and pollutant particles. The aim of this study was to analyze the dynamics of hydrosedimentological Poxim-Açu/SE river basin by monitoring water quantity and quality. Thus, we intended to present the general characteristics on the environment and sustainability contemplating systemic method in studies of interdisciplinary slant facing watersheds. We used the SWAT model in this study. We have also chosen four usage scenario and ground cover for the watershed. In the survey highlighted that the watershed of river Poxim Acu presents potential areas in the production process of sediments that are linked to both the use and occupation of land, as the topography of the land, and limiting how much water production, since there are few areas covered by native vegetation, where agriculture and pasture dominate the landscape by adding 84% of the occupied area. Mention was also made by using the parameters analyzed the good quality of the river water Poxim-Açu, being classified as Class 1, requiring only simple treatment as determined by CONAMA Resolution 357/05 for this type of class. Regarding the environmental profile of the villagers and Caroba Cajueiro, it was found that the male nature is intense, but respondents still perceive the environment as something separated from the experience of each.